C-Band 200 Gbit/s/λ PS-PAM-8 Transmission Over 2-km SSMF for Optical Interconnections - Xuancheng Huo; Meng Xiang; Gai Zhou; Jilong Li; Jianping Li; Yuwen Qin; Songnian Fu (IEEE Photonics Journal, 2024)
Driven by the exponential increase of network traffic, the demand for the capacity enhancement of photonic data-center interconnection (DCI) becomes more and more urgent. The utilization of high-order modulation format is ideally preferred to enhance the transmission capacity, considering the bandwidth constraint of optoelectrical devices. Whereas, using high-order modulation format also imposes stringent requirement on signal-to-noise ratio (SNR). By introducing probabilistic shaping (PS) technique, we can realize a shaping gain as well as adaptive data rate for the photonic DCI. Nonetheless, when PS is employed for the intensity modulation direct detection (IMDD) system, the optimal probability shaping distribution is not compatible with the distribution of forward error correction (FEC) code. Here, we derive a new probability mass function (PMF) suitable for the IMDD system to realize the cooperation of PS and FEC, based on the establishment of Lagrange function. In comparison with the uniformly distributed eight-level pulse amplitude modulation (PAM-8) signal, a certain generalized mutual information (GMI) gain can be experimentally achieved utilizing Optimized pairwise Maxwell-Boltzmann PAM-8 (Optimized PMB-PAM-8) with derived PMF under the condition of same bit-rate. After 2-km standard single-mode fiber (SSMF) transmission, the net data rate can be increased from 197 Gbit/s of uniformly distributed PAM-8 to 212 Gbit/s by the use of Optimized PMB-PAM-8, which can satisfy the requirement of 200G per lane optical interconnections.